Ultra-Weak Chemiluminescence Enhanced by Cerium-Doped LaF3 Nanoparticles: A Potential Nitrite Analysis Method - Wang, Yufei; Wang, Yanran; Huang, Chunxia; Chen, Tianyou; Wu, Jing (Frontiers in Chemistry, 2020)
In this work, cerium-doped LaF3 nanoparticles (Ce NPs) were successfully synthesized and characterized. Its chemiluminescence (CL) property was studied and amazedly found that it intensely enhanced the ultraweak CL of NaNO2-H2O2 system. The CL mechanism was systematically investigated and suggested to be the recombination of electron-injected and hole-injected Ce NPs. The new CL system was developed to be a facile, original and direct method for nitrite analysis. Experimental conditions were optimized and then satisfactory linear relationship between CL intensity and nitrite concentration was obtained. This work introduced a new pathway for the research and application of traditional fluoride NPs doped with RE3+.